Investigation of the Impact of the Pumping Beam Waist Size and Position on the Efficiency of YVO4/Nd : YVO4/YVO4 Laser Generation - Mlynczak, Jaroslaw; Zyskowski, Maciej (International Journal of Optics, 2021)
This article presents the results of the investigation of the generation efficiency for different sizes and positions of the pumping beam waist inside the active medium of the YVO4/Nd : YVO4/YVO4 lasers. The measurements were carried out for a fixed resonator length of 36.1 mm, a constant pumping power of 1.16 W, and four output couplers with different radii of curvature. According to the knowledge of the authors, such an extended experimental approach is presented for the first time.